FAO fisheries report; N.572, Supplement (FAO, 1997)
The book describes and analyses shrimp culture development and management including legal and institutional aspects and government policies of several of the main producing countries, accounts of current activities and views on shrimp culture by several intergovernmental and non-governmental organizations, and a review of the literature on this subject focusing on development economics and socio-economics issues.